Thermally activated delayed fluorescence with dual-emission and pressure-induced bidirectional shifting: cooperative effects of intramolecular and intermolecular energy transfer. Issue 5 (9th January 2023) - Zhao, Chenyue; Ding, Zhipeng; Zhang, Yibin; Ni, Zhigang; Li, Shijun; Gong, Shaolong; Zou, Bo; Wang, Kai; Yu, Ling
Abstract : A high-contrast luminescent material exhibits dual-emission and pressure-induced bidirectional shifting, originating from the cooperative effects of TADF and excimers. It provides a novel mechanism for the piezochromic behavior. Abstract : Different from the conventional piezochromic materials with a mono-redshift of single emission, our well-designed molecule demonstrates a sensitive turn-on and color-tunable piezochromic luminescence in response to the hydrostatic pressure. The molecule PXZ-W-SOF possesses dual-emission and pressure-induced bidirectional shifting characteristics. On the basis of in-depth experimental studies, on one hand, it is confirmed that the origin of the dual-emission behavior is the intramolecular charge transfer, namely thermally activated delayed fluorescence (TADF), and the intermolecular excimer; on the other hand, the emission of the excimer exhibits three-step variations with increasing pressure, which is mainly attributed to the molecular structure and its crystal packing state. The remarkable color change of PXZ-W-SOF from sky-blue to green to deep-blue during the whole process of boosting and releasing pressure is a result of intramolecular and intermolecular energy-transfer interactions. The PXZ-W-SOF molecular model is an extremely rare example of highly sensitive fluorescence tuning driven by TADF and excimer conversion under mechanical stimulation, thus providing a novel mechanism for the field of piezochromism. The unique molecular design also offers a new idea for rare deep-blue and ultraviolet TADF materials.